Role of oxygen vacancies and interstitials on structural phase transition, grain growth, and optical properties of Ga doped TiO2 - Khatun, Nasima; Tiwari, Saurabh; Vinod, C. P.; Tseng, Chuan-Ming; Liu, Shun Wei; Biring, Sajal; Sen, Somaditya (Journal of Applied Physics, 2018)
A systematic study on the effect of gallium (Ga) doping (0 <= x <= 0.10) on the structural phase transition and grain growth of TiO2 is reported here. X-ray diffraction spectroscopy and Raman spectroscopy confirm that Ga doping inhibits the phase transition. Activation energy increases from 125 kJ/mol (x = 0.00) to 300 kJ/mol (x = 0.10) upon Ga incorporation. X-ray photoelectron spectroscopy shows the presence of Ti3+/Ga3+ interstitials, substitution (Ti4+ by Ga3+), and oxygen vacancies in the samples. At lower doping (x <= 0.05), interstitials play a more significant role over substitution and oxygen vacancies, thereby resulting in a considerable lattice expansion. At higher doping (x >= 0.05), the effect of interstitials is compensated by both the effect of substitution and oxygen vacancies, thereby resulting in relatively lesser lattice expansion. Inhibition of the phase transition is the result of this lattice expansion. The crystallite size (anatase) and particle size (rutile) both are reduced due to Ga incorporation. It also modifies optical properties of pure TiO2 by increasing the bandgap (from 3.06 to 3.09 eV) and decreasing the Urbach energy (from 58.59 to 47.25 meV). This happens due to regularization of the lattice by the combined effect of substitution/ interstitials and oxygen vacancies. Published by AIP Publishing.